PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH PENURUNAN TARIF PAJAK (DISKON PAJAK) - Oma Romantis; Kurnia Heriansyah; Soemarsono D.W; Widyaningsih Azizah (Jurnal Ilmiah Akuntansi dan Manajemen, 2020)
The aims of this study to examine the effect of tax planning on earnings management which is moderated by reducing tax rates (tax discounts). The population in this study are companies listed in the 2017-2018 LQ45 index. The sampling technique in this study used a purposive sampling method with predetermined criteria, in order to obtain a total sample of 23 companies with final data totaling 46 financial statements. The type of data is secondary data obtained from www.idx.co.id. The analysis technique used in this study is panel data regression analysis and is processed using the Eviews 9.0 program. The results of this study indicate that tax planning has a significant effect on earnings management with a negative coefficient direction. A reduction in tax rates (tax discounts) weakens the effect of tax planning on earnings management.